Il paratesto del romanzo web in Cina: il caso Punto di partenza (ENTHYMEMA, 2023)
In the People's Republic of China, during the last twenty years, online literature has emerged as a form of popular literature and long novels published and daily updated by users are the main form of fiction circulating on online platforms. Using concepts developed by Gérard Genette, this article analyzes the paratext of some web novels published on Starting Point and especially the contents within the section "related to the text," a space preceding the novel in which writers publish different kinds of news and information. The analysis of these contents highlighted some practices and strategies within the relationship between the subjects involved in this form of literature and confirmed the centrality of readers and the virtual community.
Keywords: Online Literature; Chinese Online Literature; Online Novel; Paratext; Writer-Reader Relationship